Effect of the topology on the mechanical properties of porous iron immersed in body fluids. (May 2021) - Salama, MC; Rechena, D; Reis, L; Deus, AM; Santos, C; Carmezim, MJ; Vaz, MF
A new generation of biodegradable metal alloys with a porous structure has been receiving growing attention as temporary bone scaffolds for tissue regeneration. The mechanical response of the scaffolds depends upon several factors including the properties of the metal itself, the amount of porosity, the geometrical topology and the immersion conditions. The purpose of this study is to evaluate the degradation behaviour and the mechanical properties of porous iron samples with porosities in the range of 20–30%. Besides the amount of porosity, the effect of topology was evaluated with the study of different arrangement of pores, as well as pore shapes. The specimens were subjected to chemical degradation by immersion of the iron samples in body fluid simulation conditions. The mechanical properties of the samples prior and after the degradation process were assessed by three-point bending tests. Numerical simulations were carried out and the results were compared with the experimental results. The degradation operated by body fluids tends to reduce the mechanical properties. In comparison with the compact structures, porous structures exhibit lower mechanical strength, but still with reasonable values for the use in temporary implants, which also allows reducing the stress shielding effect, keeping the biodegradable advantages. The present work also confirms that the topological design has a strong influence on the mechanical properties of the specimens and on the biodegradation behaviour.